XRF elemental analysis of inks in South American manuscripts from 1779 to 1825 - Celina Luízar Obregón (2021)
The Regional Archive of Cusco in Peru guards valuable history collections with exceptional regional and international value dating from the sixteenth century to the present. Historical manuscripts are part of the identity of all people; they constitute a tangible cultural heritage that must be studied, valued, and protected. In this sense, the objective of this research was to identify the chemical compositions of inks and paper, with the goals of setting the background of their originality, identifying relationships between them, and glimpsing antecedents that generated degradation due to the compositions of the inks. This study is the first of its kind in Peru and reveals the chemical elements present in the writing ink, the seal, and the paper of five documents from the late eighteenth and early nineteenth centuries. Duplicate in situ nondestructive analyses were carried out using a hand-held X-ray fluorescence spectrometer under ambient conditions in soil mode, configured with three sequential shots, and energies from zero to 40, 40, and 15 keV, respectively. The elements S and Fe were present as components of iron gall inks. Cu and Zn were less abundant; probably, they provided less corrosion and more color intensity to the inks. The minor elements Pb, As, and especially Ag in all manuscripts differentiate them from European inks of the same period. Additionally, the five documents reflect the same elemental compositions but with different concentrations. This could mean that writers used local raw materials and Spanish ink recipes. Finally, the analyses of standard reference material, SRM 1646a and SRM 196b, gave results with acceptable precision.